Using of surface back pressure with water based mud in managed pressure drilling technique to solve lost circulation problem in Southern Iraqi Oil Fields - Dhayea, Batool Abdullah; Almahdawi, Faleh. H. M.; Al-Shaibani, Sinan I. M. (Journal of Petroleum Research and Studies, 2021)
Many drilling problems are encountered continuously while drilling oil wells in the southern Iraqi oil fields. Many of these problems are ineffectively handled resulting in a longer non-productive time. This study aims to identify the formations such as Dammam, and Hartha formations،diagnose potential problems and provide the solution for lost circulation problem. After conducting a comprehensive study on the subject and based on available data, previous studies and some information, the managed pressure drilling (MPD) method was the best technique to solve this problem. This process may use various techniques including control of back pressures .Thus, reducing the risk and control the costs of drilled wells, which have narrow pressure window by managing the wellbore pressure profile. The well plan software program provided by Halliburton Company was used, this software is based on a database and data structure common to many of Landmark’s drilling applications. Mud used with various injection rates to choose the rate that provides the conditions to achieve the best drilling process, as it using mud weights of (8.8 -8.7 ) ppg and applied a surface back pressure (50 psi). Depending on specifications of second hole the optimal injection rate was chosen using the (hydraulics) program. As a results, rate of water injection (850) gpm, is the best which it provides a good efficient cutting transport ratio (CTR), which means high stability and preventing formation damage in addition to controlling in mud losses